Assessing the Merits of a PPI Trial-Based Diagnosis for Gastroesophageal Reflux Disease: Speculations on Efficacy and Pitfalls. Issue 2 (June 2021) - Kamal, Afrin N.; Zikos, Thomas A.; Clarke, John O.
Gastroesophageal reflux disease is a highly prevalent condition which can lead to complications in affected individuals. Given the economic implications of widespread testing, there has been interest in a symptom-based approach to diagnosis and use of short-term empiric acid suppressive therapy as a diagnostic modality. This review will highlight the background with regards to these clinical questions, the data regarding performance characteristics of establishing a symptom-based reflux diagnosis (focusing on typical, atypical, and extra-esophageal symptoms), the merits of the so-called "PPI Trial" and potential pitfalls to consider when seeing patients with suspected reflux symptoms.